Cultural defense, hate crimes and equality before the law - Jean-Christophe Merle (Ethic@: an International Journal for Moral Philosophy)
The so-called “cultural defense” before the courts, which seeks full or partial exculpation based on the cultural identity of either the defendant or the plaintiff, and the newly established category of “hate crimes”, which enhances the criminal sentences in cases in which the criminal acts from motives of prejudice, are two examples – tending in opposite directions – for culturally based exceptions to the principle of equal enforcement of the law, the intent of which is to treat everybody as an equal. The justification for these departures from equal enforcement is that the law is allegedly biased infavor of the cultural majority within the population. However, if one accepts this claim, one should (i) complement these measures by creating a consistent set of rights and duties for the cultural communities, (ii) limit these rights and duties to a merely legal, not comprehensive culture, (iii) subject it to legislative review and (iv) define clear legal relationships between the cultural communities. The “personal status” of traditional as well as of new cultural communities (both with membership on a voluntary basis and under the respect of Mill’s “no harm principle”) may provide us with elementsof a real equal treatment of individuals belonging to different cultures.